Medical microbiology - Murray, Patrick R (Mosby, 2002)
Succinct and focused, this book presents today\'s most important facts and information about the microbes that cause diseases in humans. This text delivers balanced coverage of immunology, bacteriology, virology, mycology, and parasitology in a user-friendly and organized format, with an emphasis on teaching the student to think like a doctor. An extensive 4-color art program illustrates the text. The 4th Edition has been meticulously revised and updated to incorporate new knowledge, new treatments, and new illustrations.
Keywords: Parasitology; mikrobiologie, lékařská mikrobiologie; mikrobiologické techniky; Laboratorní technika; mikrobiologie; Mikrobiologie; parazitologie; Microbiology; Microbiological Techniques